A large barrier single-molecule magnet without magnetic memory12. Issue 29 (1st July 2019) - Giansiracusa, Marcus J.; Al-Badran, Susan; Kostopoulos, Andreas K.; Whitehead, George F. S.; Collison, David; Tuna, Floriana; Winpenny, Richard E. P.; Chilton, Nicholas F.
Abstract : We report a six coordinate Dy III single-molecule magnet (SMM) with an energy barrier of 1110 K for thermal relaxation of magnetization, but no magnetic hysteresis above 2 K. Abstract : We report a six coordinate Dy III single-molecule magnet (SMM) with an energy barrier of 1110 K for thermal relaxation of magnetization. The pure compound shows no retention of magnetization even at 2 K.